2012
DOI: 10.1016/j.celrep.2012.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Immune Tolerance to Tumor Antigens Occurs in a Specialized Environment of the Spleen

Abstract: Peripheral tolerance to tumor antigens (Ags) is a major hurdle for antitumor immunity. Draining lymph nodes are considered the privileged sites for Ag presentation to T cells and for the onset of peripheral tolerance. Here, we show that the spleen is fundamentally important for tumor-induced tolerance. Splenectomy restores lymphocyte function and induces tumor regression when coupled with immunotherapy. Splenic CD11b(+)Gr-1(int)Ly6C(hi) cells, mostly comprising proliferating CCR2(+)-inflammatory monocytes with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
223
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 191 publications
(245 citation statements)
references
References 41 publications
18
223
1
Order By: Relevance
“…The suppression assay demonstrated that the in vitro inhibitory function of graft infiltrating Ly6Clo macrophages is confined to the proliferating S/G2/M subset. This is consistent with our previous collaborative finding, which demonstrated that suppressive monocytic-derived cells from tumor bearing mice are highly proliferative (24). …”
Section: Resultssupporting
confidence: 94%
“…The suppression assay demonstrated that the in vitro inhibitory function of graft infiltrating Ly6Clo macrophages is confined to the proliferating S/G2/M subset. This is consistent with our previous collaborative finding, which demonstrated that suppressive monocytic-derived cells from tumor bearing mice are highly proliferative (24). …”
Section: Resultssupporting
confidence: 94%
“…6C), while leaving the Gr1 hi , Gr1 lo , and Gr1 À cells unaffected compared with contraimmunized and control mice. Interestingly, Gr1 int MDSCs were recently shown to be the most immunosuppressive MDSCs in tumor-bearing mice (36). Furthermore, we observed that significantly more MHCII þ -expressing CD11b þ Gr1 þ MDSCs infiltrated the tumors of tdLN-targeted (ipsi) mice compared with control and non-tdLN-targeted (contra) mice, suggesting maturation of MDSCs (Fig.…”
Section: Targeting the Tdln With Nanoparticle-conjugated Ova And Cpg supporting
confidence: 49%
“…6). While we previously showed that tumorinfiltrating monocytic MDSCs are NP þ , delivering our model cancer vaccine to the tdLN decreased the number of tumorresident Gr1 int MDSCs, which are described as monocytic and the most immunosuppressive subset, and led to MDSC maturation, thus making them less suppressive (21,36,48). CpG has been shown to affect the phenotype of MDSCs, especially monocytic MDSCs, in tumor-bearing mice, but at much higher CpG doses than we used here (32,49).…”
Section: Discussionmentioning
confidence: 94%
“…Because the key role of the spleen for tumor-induced tolerance mediated by MDSCs has been recently demonstrated in a thymoma and mammary mouse model (19), we focused our attention on the splenic microenvironment of AOM/DSS-treated tumor-bearing mice, in which the two cell populations also were found in close proximity (Fig. 1F).…”
Section: Mast Cells Potentiate Monocytic Mdsc-suppressive Properties mentioning
confidence: 99%